Labor Supply and Automation Innovation - Alexander M. Danzer; Carsten Feuerbaum; Fabian Gaessler (Institute of Labor Economics (IZA), 2020)
While economic theory suggests substitutability between labor and capital, little evidence exists regarding the causal effect of labor supply on inventing labor-saving technologies. We analyze the impact of exogenous changes in regional labor supply on automation innovation by exploiting an immigrant placement policy in Germany during the 1990s and 2000s. Difference-in-differences estimates indicate that one additional worker per 1,000 manual and unskilled workers reduces automation innovation by 0.05 patents. The effect is most pronounced two years after immigration and confined to industries containing many low-skilled workers. Labor market tightness and external demand are plausible mechanisms for the labor-innovation nexus.
Keywords: O31; O33; J61; 330; labor supply; automation; innovation; patents; labor market tightness; quasiexperiment